2014
DOI: 10.1001/jamainternmed.2014.4506
|View full text |Cite
|
Sign up to set email alerts
|

Use of Internist's Free Time by Ambulatory Care Electronic Medical Record Systems

Abstract: ethnic minorities. 1 The lower initial uptake of the GDDP among racial/ethnic minorities raises the question: why would patients who gain more from GDDPs be less likely to use them? We aimed to determine whether the uptake of the GDDP increased as the program matured and to examine whether factors affecting the uptake of the GDDP have remained steady over time. Methods | The Medical Expenditure Panel Survey is a nationally representative longitudinal household survey of health care use and expenditures for non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 4 publications
1
42
0
Order By: Relevance
“…Even when data are appropriately stored, it can be timeconsuming to manually search multiple sections of the EHR to obtain necessary CKD-related data during a patient visit (34). EHRs could offer provider-facing flow sheets to display all important CKD-related data in one location.…”
Section: Ckd-related Data In Ehrs Should Be Readily Available and Easmentioning
confidence: 99%
“…Even when data are appropriately stored, it can be timeconsuming to manually search multiple sections of the EHR to obtain necessary CKD-related data during a patient visit (34). EHRs could offer provider-facing flow sheets to display all important CKD-related data in one location.…”
Section: Ckd-related Data In Ehrs Should Be Readily Available and Easmentioning
confidence: 99%
“…[2][3][4][5][6] Factors such as increased structured documentation requirements, computerized physician order entry (CPOE), inbox management, patient portals, and a redistribution of tasks previously performed by clinical staff to clinicians has led to more work that is not direct face time with patients. [7][8][9][10][11] A 2016 study showed physicians from family medicine, internal medicine, cardiology, and orthopedics spent nearly 2 hours in the EHR and on other desk work for every 1 hour of direct patient care. 7 In our own primary care system during 2013-2016, despite a stable 2.2 average office visits per panel member per year, telephone calls increased by 3% and MyChart portal encounters increased by 62% to an average of 0.66 per panel member per year.…”
Section: Introductionmentioning
confidence: 99%
“…1 Reviews of the effect of EHRs on patient and physician outcomes have been mixed, including neutral to small positive effects on common quality metrics and disease-specific guidelines, 2-5 mixed on office workflow, 2,6,7 and mostly decreased on primary care physician productivity. [8][9][10] There is little to no evidence that patient outcomes are improved or overall health care costs are reduced.…”
mentioning
confidence: 99%